Droplets Fusion in a Microchannel on a Piezoelectric Substrate - Fu Xiang-ting; Zha Yan; Zhang An-liang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Fusion droplets is a key operation in a microfluidic device for microfluidic analysis. A new fusion method for droplets was presented. An interditigal transducer and a reflector were fabricated on 1280-yx LiNbO3 piezoelectric substrate using microelectric technology. A poly-dimethyl silicone micro-channel was made by soft lithography technology and mounted on the piezoelectric substrate. Droplets in the microchannel were actuated by surface acoustic wave and fussed each other. Coloured dye solution droplets were used to fusion experiments. Results show that the two droplets in the microchannel can be fused by help of surface acoustic wave, and size of droplets, distance of droplets and RF signal power can affect successful fusion of the droplets. The fusion method is valuable for microlfuidic biological and chemical analysis in a microfluidic device. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2826